Phase-sensitive individualized pharmacotherapy for alcohol use disorder - Müller, Christian P.; Lenz, Bernd; Kornhuber, Johannes; Ebner-Priemer, Ulrich W.; Schwarz, Emanuel; Ersche, Karen D.; Kiefer, Falk; Spanagel, Rainer (Neuropharmacology, 2026)
Alcohol use disorder (AUD) is a prevalent psychiatric disorder that continually causes significant suffering. Although pharmacotherapies are available, they have low efficacy and show little compliance. Thus, new approaches for AUD treatment are still needed. The core symptoms of AUD include drug seeking, consumption, and withdrawal, which occur in distinct shifted time phases. Recent neurobiological research has revealed that these phases have rather unique underlying neurobiological processes and neuropharmacology. We propose a new treatment strategy based on available pharmacotherapies with small effects on individual AUD phases and independent advancements in diagnosis tool technology. The strategy combines a pharmacological toolbox with an ecological momentary assessment (EMA) tool. An artificial intelligence-coupled EMA device is provided to patients and can act as a near real-time diagnostic monitor, a phase-sensitive individualized treatment guide, and a metric for therapeutic success. The EMA tool will allow highly individual AUD phases to be targeted with tailored neuropharmacology in near real time. This approach may revolutionize the pharmacotherapies used for mental disorders.
CRIS-Team Scopus Importer:2025-11-07
Keywords: Alcohol use disorder; Ecological momentary assessment; Pharmacotherapy; Phase-sensitive treatment